Alternative Criminal Punishments for Completion of Misdemeanor Crimes with Social Justice - Serimin Pinem (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
The vision of the development of national law is "the realization of a just and democratic rule of law through the development of a national legal system that serves the interests of the people and the nation to protect all people and the nation, as well as the blood of Indonesia, promotes public welfare, develops the life of the nation and participates in carrying out peace a world based on independence, eternal peace and social justice based on the Pancasila and the 1945 Constitution. Enforcement of criminal law and punishment should no longer be seen as the only hope of being able to resolve or overcome crime completely, because in essence crime is a "problem humanity "and" social problems ", which cannot be solved solely by criminal law. As a social problem, crime is a dynamic social phenomenon that is always growing and is related to other very complex phenomena and social structures. One way to realize social order is by applying alternative criminal penalties for minor crimes.